New way for maxillary nerve block: a technical note. (17th October 2020) - Cerrato, Alessia; Zanette, Gastone; Bacci, Christian
Abstract: Aim: To describe a technique for the block of the maxillary nerve simpler than those currently present in the literature Methods: Maxillary nerve block is used to induce regional anaesthesia in the areas innervated by the second branch of the trigeminal nerve. It can be achieved at the point where the maxillary nerve passes through the pterygopalatine fossa, which is accessible via the oral cavity, or using the greater palatine canal technique, or an extra‐oral approach via the maxillary tuberosity. Results: In this technical note, we describe a maxillary nerve block involving a method that is easy to implement, and that draws on the maxillary tuberosity approach but relies on more precise landmarks. Conclusion: The block of the maxillary nerve is useful in order to obtain a perfect analgesia in the surgeries that require it, but it is not widely used because of its technical difficulty. This technical note may simplify the procedure.